VOID CONTENT IN POLYMER COMPOSITE MATERIALS, THEIR NATURE OF AND WAYS TO MINIMIZE THEIR PRESENCE - Shatylo, Serhii (Problems of Friction and Wear, 2025)
This article is an insight on the topic void content and associated hygroscopicity of polymer composite materials (PCM), made of carbon and glass fibers, their influence on mechanical strength and provides ways to minimize such influence of those phenomena on final characteristics of parts, made out of these materials. The issue of porosity and hygroscopicity of PCM materials becoming more relevant with more searches of engineering solutions for the introduction of such materials into fluid systems of the vehicles. A disclosure is given about the influence of above-mentioned phenomena on characteristics of carbon and glass fiber PCMs, as those are main fibers used in aviation industry. A number of technologies of manufacturing parts from such fibers is provided and their void content percentage is described.